(untitled) (World Science, 2021)
80 pregnant women were examined after assisted reproductive technology (ART) programs: 40 women with manifestations of intrahepatic cholestasis of pregnant women (IHP) - the main group and 40 women without manifestations of IHP (comparison group).In the majority (62.5%) of patients after ART, the diagnosis of IHP established after 30 weeks of pregnancy. Some patients (27.5%) reported short-term episodes of IHP up to 24 weeks of gestation. In 17.5% of women, IHP had a severe course. Almost a third (27.5%) of women are over 35 years old. Women with IHP have a significantly higher frequency of allergies in the anamnesis (35.0%), liver pathology (20.0%) and diseases of the gastrointestinal tract (25.0%). In one third of women, IHP developed repeatedly, 42.5% of the main patients indicated a family history burdened with IHP. Almost a third of women (27.5% vs. 12.5%, p<0.05) had a history of polycystic ovary syndrome.The current pregnancy characterized by a high frequency of complications. A quarter of patients (25.0%) had early preeclampsia. In the second half of pregnancy, the threat of preterm birth noted in most women during the manifestation of IHP (60.0%). The incidence of fetal distress in women with IHP was almost 2 times higher than in patients without this complication (47.5% vs. 25.0%, respectively, p <0.05). The frequency of preeclampsia is also higher (40.0%).The vast majority of women in the main group were born by cesarean section (70.0%). Almost half of patients with IHP were premature (45.0%). A third of women (35.0%) had fetal distress in childbirth. In 27.5%, childbirth complicated by bleeding of more than 5% of body weight. The postpartum period was characterized by a 4-fold increase in the frequency of late bleeding (20.0% vs. 5.0%, p <0.05).One case of antenatal mortality noted in pregnant women after ART with IHP. Almost half of the children were born with asphyxia of varying severity (48.7%), with 10.3% diagnosed with severe asphyxia. One third of children were born with a body weight below 2500 g (30.8%). In 74.4% of newborns from mothers of the main group, various disorders of the period of early neonatal adaptation were noted, among which the most prominent were: RDS (35.9%), jaundice (43.6%) and gastrointestinal syndrome (30.8%). The 2-fold increased incidence of hemorrhagic syndrome (17.9%) is noteworthy.